Regulation of senescence associated signaling mechanisms in chondrocytes for cartilage tissue regeneration. Issue 2 (February 2016) - Ashraf, S.; Cha, B.-H.; Kim, J.-S.; Ahn, J.; Han, I.; Park, H.; Lee, S.-H.
Summary: Adult articular chondrocytes undergo slow senescence and dedifferentiation during in vitro expansion, restricting successful cartilage regeneration. A complete understanding of the molecular signaling pathways involved in the senescence and dedifferentiation of chondrocytes is essential in order to better characterize chondrocytes for cartilage tissue engineering applications. During expansion, cell fate is determined by the change in expression of various genes in response to aspects of the microenvironment, including oxidative stress, mechanical stress, and unsuitable culture conditions. Rapid senescence or dedifferentiation not only results in the loss of the chondrocytic phenotype but also enhances production of inflammatory mediators and matrix-degrading enzymes. This review focuses on the two groups of genes that play direct and indirect roles in the induction of senescence and dedifferentiation. Numerous degenerative signaling pathways associated with these genes have been reported. Upregulation of the genes interleukin 1 beta ( IL-1β ), p53, p16, p21, and p38 mitogen-activated protein kinase ( MAPK ) is responsible for the direct induction of senescence, whereas downregulation of the genes transforming growth factor-beta ( TGF-β ), bone morphogenetic protein-2 ( BMP-2 ), SRY (sex determining region Y)-box 9 ( SOX9 ), and insulin-like growth factor-1 ( IGF-1 ), indirectly induces senescence. In senescent and dedifferentiated chondrocytes, it was found that TGF - β, BMP - 2, SOX9, and IGF-1 are downregulated, while the levels of IL - 1β, p53, p16, p21, and p38 MAPK are upregulated followed by inhibition of the normal molecular functioning of the chondrocytes. This review helps to elucidate the underlying mechanism in degenerative cartilage disease, which may help to improve cartilage tissue regeneration techniques.